Design optimization of high-performance inductors on silicon - Sia, Choon Beng. (2008)
This thesis aims to provide a comprehensive of the Master Engineering Research Project, Design Optimization of High Performance Inductors on Silicon. An overview of the silicon-based spiral inductor was presented with the motivation for this project. Optimizations of the inductors’ physical dimensions had been performed. The operation of shielded inductors was closely examined.